AN EVALUATION OF GOOD CORPORATE GOVERNANCE IMPLEMENTATION (Case Study in PT. Pelabuhan Indonesia III (Persero) Surabaya) - Sari, Renzy Permata; Irianto, Gugus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aimed to evaluate the application of Good Corporate Governance in PT. Pelabuhan Indonesia III (Persero) Surabaya which has been implemented since 2003. A case study is used as a method and design to answer the research questions. Data collection methods used in the study are interviews, observation, and documentation. This study used descriptive and qualitative analysis to interpret the data through GCG scorecard results on the company. The results of this study indicate that: (1) The application of good corporate governance principles of which include transparency, accountability, responsibility, independency and fairness in the PT. Pelabuhan Indonesia III (Persero) Surabaya has implemented well although there are some indicators that have not been applied. One of them is the lack of a whistle blowing system on corporate website. (2) There is no significant difference in GCG Scoring based on FCGI and assessment by external auditor.Key words: Good Corporate Governance, Scorecard GCG